Acute lymphoblastic leukemia in patients with Down syndrome with a previous history of acute myeloid leukemia. Issue 8 (24th December 2016) - Tomizawa, Daisuke; Endo, Akifumi; Kajiwara, Michiko; Sakaguchi, Hirotoshi; Matsumoto, Kimikazu; Kaneda, Makoto; Taga, Takashi
Abstract: Patients with Down syndrome (DS) are predisposed to acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL) in early and later childhood, respectively, but rarely experience both. We herein discuss four patients with DS with ALL and a history of AML who were treated with various chemotherapies, one of whom later received a bone marrow transplantation. Three patients survived and remain in remission. One patient died of fulminant hepatitis during therapy. No common cytogenetic abnormalities in AML and ALL besides constitutional +21 were identified, indicating that the two leukemia types were independent events. However, the underlying pathomechanism of these conditions awaits clarification.